BENEVOLENT SEXIST TENDENCIES IN GENDER ASSESSMENT IN THE ENGLISH TERM OF ENDEARMENT “BABY” AND ITS VARIATIONS - Nikolaishvili, Sofia (Online Journal of Humanities ETAGTSU, 2021)
The present article aims to analyze benevolent sexist tendencies in the process of gender assessment in the English term of endearment “baby” and its variations. Representing the social, cultural and psychological aspects of a particular linguistic community, studying address terms closely, terms of endearment among them, can reveal much about language and people. The data for the study is retrieved from the online surveys specifically made for the research about the relationship between this aspect of language and gender. The results align with the theories of benevolent and indirect sexism, as well as with the results of other studies about gender and language conducted by scholars interested in this topic. <a title="Benevolent Sexist Tendencies in Gender Assessment in the English Term of Endearment “Baby” and its Variations" href="https://etag.tsu.ge/journal/files/06_Sofia-Nikolaishvili.pdf" target="_blank" rel="noopener">Full Text (PDF)